Impact of Agro-forestry on Soil Conservation in Kayonza Subcounty: A Case Study of Rutendere Parish. - Ayebale, Anxious (Kabale University., 2024)
The study evaluated the impact of agroforestry on soil conservation in the Kayonza sub-county Rutendere parish of Uganda. The objectives of the study were, to find out different economic activities that contribute to soil degradation and other methods of soil conservation other than agroforestry, and to find out different agro-forestry tree species that contribute to soil productivity in the Kayonza sub-county. The study used a case study research design and a sample size of 320 respondents was used for the study. The sampling techniques used included simple random sampling and purposive sampling techniques and findings were collected using the interview method, questionnaire method, and observation method. The study focused mainly on the effectiveness of agroforestry and its impacts on soil conservation. It also revealed the reality of agroforestry as a common practice in Rutendere Parish and other economic activities responsible for soil degradation Rutendere parish as obtained from three hundred and twenty respondents indicated that where agroforestry as a soil conservation technique was not commonly practiced, the area was exposed to wearing of land surface by erosion, soil quality depreciation, loss of nutrient-rich top layer, the soil degraded and low agricultural productivity However agricultural productivity was high where agroforestry and other soil conservation practices such as mulching, cover cropping, and terracing were commonly practiced in Rutendere Parish Kayonza Sub-County. The study recommended that farmers should be highly sensitized and mobilized to attend seminars and agricultural talks, the government should encourage the farmers in Rutendere Parish the formation of farmer groups through which grants could be given inform about seedlings and other useful inputs, and adult education should be encouraged to enhance conservation and diversify farming system as against mono-cropping system which compromise soil to nutrient loss and soil degradation.